2013
DOI: 10.1016/j.exer.2012.10.010
|View full text |Cite
|
Sign up to set email alerts
|

An MIP/AQP0 mutation with impaired trafficking and function underlies an autosomal dominant congenital lamellar cataract

Abstract: Autosomal dominant congenital cataracts have been associated with mutations of genes encoding several soluble and membrane proteins. By candidate gene screening, we identified a novel mutation in MIP (c.494 G>A) that segregates with a congenital lamellar cataract within a South Indian family and causes the replacement of a highly conserved glycine by aspartate (G165D) within aquaporin0 (AQP0). Unlike wild type AQP0, expression of AQP0-G165D in Xenopus oocytes did not facilitate swelling in hypotonic medium. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 25 publications
5
26
0
Order By: Relevance
“…Similarly, Prior studies of mutant MIP proteins have shown a loss of water permeability function and impaired trafficking in expression systems [43], [44]. Our findings were consistent with the results of Senthil Kumar et al [43], who identified the G165D MIP mutation and confirmed that this mutant was involved in congenital lamellar cataracts in a South Indian family. In addition, the expression of MIP and G165D-MIP in Xenopus oocytes and Hela cells suggested that substitution of the conserved glycine residue leads to improper trafficking of AQP0 and destruction of water channel function.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Prior studies of mutant MIP proteins have shown a loss of water permeability function and impaired trafficking in expression systems [43], [44]. Our findings were consistent with the results of Senthil Kumar et al [43], who identified the G165D MIP mutation and confirmed that this mutant was involved in congenital lamellar cataracts in a South Indian family. In addition, the expression of MIP and G165D-MIP in Xenopus oocytes and Hela cells suggested that substitution of the conserved glycine residue leads to improper trafficking of AQP0 and destruction of water channel function.…”
Section: Discussionsupporting
confidence: 92%
“…(Arg140*)---PRef [37]F#7F2 monthsUnknown type, nystagmus-AD MIP NM_012064.3 c.494G>Ap. (Gly165Asp)Aquaporin-likeD, D, D-PRef [17]S#4F3 monthsTotal cataract, nystagmus-Sporadic->new AD MIP NM_012064.3 c.530A>Gp. (Tyr177Cys)Aquaporin-likeT, D, D-PRef [18]F#8FBirthUnknown type, nystagmus-AD MIP NM_012064.3 c.612C>Gp.…”
Section: Resultsmentioning
confidence: 99%
“…Two variants were familial and the third was a sporadic case of pediatric cataract. While the two missenses mutations, c.530A > G; p.(Tyr177Cys) and c.494G > A; p.(Gly165Asp), have been previously described [17, 18], the nonsense mutation c.612C > G; p.(Tyr204 * ) in family #8 is a novel variant (Fig. 4d), it might prevent MIP protein transport and reduce the formation of available water channels as well as p.(Lys228Glufs*4), which recently reported by Long X [19].…”
Section: Resultsmentioning
confidence: 99%
“…To date, 16 mutations in the MIP gene have been reported to be associate with autosomal dominant cataracts, including 10 missense mutations81315161718192021; one acceptor splice-site mutation22; one donor splice-site mutation23; one deletion that causes a frameshift at 638delG14; one initiation codon mutation24; and two nonsense mutations2526. The cataract phenotypes are significantly different among the MIP mutation families.…”
Section: Discussionmentioning
confidence: 99%